Pengembangan Model Pelatihan PTK Berbasis Pendampingan untuk Meningkatkan Profesionalitas Guru Matematika SMA di Kabupaten Brebes - Masrukhi Masrukhi; Joko Widodo; Sukestiyarno Sukestiyarno; Tri Joko Raharjo (Manajemen Pendidikan, 2016)
Classroom-based  action research (CAR) for high school math teachers is very important to develop their professionalism.  To improve the competence of teachers, a development of CAR  training  model  based  on  mentoring  is  needed.  This  study  aims  to  produce  an appropriate  CAR  training  model  based  on  mentoring  to  improve  teachers’ professionalism.  This study employed research and development (R D) model, then the procedure pursued in this research started from  (1) literature study, (2) preliminary field study,  (3)  needs  analysis,  (4)  preparing  the  training  model  design,  (5)  performing validation model, (6) revising the model, (7) preparing hypothetical model of training, (8) performing limited testing and expanded trials, and (9) revising the final model through the  focus  group  discussion   (FGD-2),  experts,  and  practitioners   to  obtain  the  final model.The   result   shows   that:  (1)  the  product   which   is  validated   by  experts   and practitioners  obtains  a mean  score  of 62.15  (good  qualification),  (2) the final  training model is very feasible to be used by the indication of the its mean score at 3.59 (very high) for its usefulness, the mean score of 3.48 (very high) for its practicality, the mean score of3.58  (very  high)  for  its  feasibility.  The  implementation   of  training  program  is  alsocapable of producing  CAR research reports. The conclusions  of research is that the final model of CAR training based on mentoring and its training instruments are very feasible to be used to improve the professionalism  of senior high school math teachers in Brebes.